Biochemical detection and characterization of Vibrio spp. in whitelag shrimp (Litopenaeus vannamei) aquaculture system - A'rifin, Nurul Maulia; Suhermanto, Achmad; Safitri, Nur Maulida; Suherman (UIN Sunan Ampel Surabaya, 2026)
Vannamei shrimp (Litopenaeus vannamei) is a major aquaculture commodity with high economic value, contributing significantly to foreign exchange earnings. Suboptimal management of the aquaculture environment can promote the proliferation of pathogens, particularly Vibrio spp., leading to production losses from vibriosis. This study aimed to biochemically characterize Vibrio spp. isolated from vannamei shrimp aquaculture and to determine the dominant species. Water samples were collected from three brackish water aquaculture tanks in Serang, Indonesia, and cultured on TCBS agar, Hi Chrome Vibrio, and TSA media. Pure isolates were subjected to a series of biochemical tests, including Gram staining, catalase, oxidase, motility, carbohydrate fermentation, aerobic–anaerobic growth, salinity tolerance, MR-VP test, decarboxylase, indole, KCN, urease, and gas from glucose. The isolates were Gram-negative, catalase- and oxidase-positive, motile, curved bacilli, fermentative, and exhibited variations in carbohydrate fermentation patterns (glucose, sucrose, lactose). All isolates grew at 6% salinity and 37°C, with some variations in characteristics between tanks. Based on the biochemical profiles, the isolates were consistent with Vibrio parahaemolyticus, highlighting the need for proper environmental management to mitigate the risk of vibriosis in vannamei shrimp aquaculture systems. These findings underscore the importance of regular water quality monitoring and biosecurity measures to prevent disease outbreaks.